Identify the diversity of diagnostic equipment, case variations, and number of human resources in the radiology polyclinic at Ibnu Sina teaching hospital Makassar in the January-December 2022 period - Fadhillah, Fadhillah; Febie Irsandy; Prema Hapsari Hidayati; Rahmawati, Rahmawati; Muhammad Yasin Arsal (Jurnal EduHealth, 2024)
The study was conducted at Ibnu Sina Teaching Hospital Makassar to investigate the diversity of diagnostic equipment, case variations, and human resources in radiology polyclinics in the period January-December 2022. This study used a descriptive cross-sectional design with a sample of patients who had undergone radiology examinations at the polyclinic radiology and recorded in the medical records of Ibnu Sina Teaching Hospital during that period. The research results showed that the diagnostic equipment at RSP Ibnu Sina Makassar for the period January - December 2022 was 1 unit of conventional radiology, 1 unit of ultrasonography (USG), and 1 unit of computed tomography (CT-Scan). Meanwhile, human resources were recorded at 15 people, with 7 radiographers, 1 administrative person, 1 radiation protection officer, and 6 radiology specialist doctors. The most cases were bronchitis 595 (20.93%) and hypertension heart disease 667 (23.46%) in the chest x-ray examination type, cholelithiasis 119 (13.84%) and fatty liver 116 (13.49%) in the ultrasound examination type. abdomen, and adnexal tumors or ovarian tumors 274 (42.35%) in the CT-Scan examination type.